PENGARUH PERCEPTION OF ORGANIZATIONAL SUPPORT TERHADAP KOMITMEN AFEKTIF PEGAWAI DIMEDIASI OLEH INTENTION TO STAY PADA PONDOK PESANTREN JABAL NUR KANDIS SIAK - At Taqi, Ghozi Asadullah; Nurfaisal Nurfaisal; Adolf Bastian (CV. Denasya Smart Publisher, 2025)
This research aims to determine the relationship between Perception of organizational support and employee Affective Commitment through Intention to Stay at the Jabal Nur Kandis Siak Islamic Boarding School. The research method used is quantitative research. The population in this study were all employees and teachers who worked at the Jabal Nur Kandis Siak Islamic Boarding School. The sampling technique used was purposive sampling, so that a sample of 89 respondents was obtained. The data collection technique used was using a structured questionnaire. The instrument testing technique in this research is validity and reliability testing using PLS (Partial Least Square) as the measurement. The results of this research show that Perception of Organization and Intention to Stay have a direct and significant effect on the Affective Commitment of Employees and Teachers who work at the Jabal Nur Kandis Siak Islamic Boarding School. Likewise, Perception of organizational support has a significant direct effect on Intention to Stay and Intention to Stay has been proven to be able to mediate the relationship between Perception of organizational support and Affective Commitment of Employees and Teachers who work at the Jabal Nur Kandis Siak Islamic Boarding School.